TANGGUNG JAWAB PERAWAT DALAM MELAKUKAN TINDAKAN MEDIS (INJEKSI VITAMIN C) DI LUAR JAM KERJA DI KABUPATEN SIAK SRI INDRAPURA - Nuraliyah, Putri; Firdaus, Firdaus; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Nurses are the most health workers in Indonesia. Nurse staff who perform nursing actions must be in accordance with nurse competencies that have been determined and obtained during the education process. Therefore, the responsibilities of nurses in carrying out nursing duties must be in accordance with nurse service standards, professional standards, operational standards, and the health needs of recipients of health services. The purpose of receiving this thesis, namely: First To find out what is the nurse responsible for medical actions outside working hours. Secondly to find out about what patients should do to the nurses in carrying out medical procedures outside working hoursThis type of research is included in Sociological Juridical research. According to Sutrisno Hadi, Sociological Juridical research is an effort to determine, develop, and test the truth of business knowledge conducted using scientific methods for research. This research was conducted and to complete the data source, the authors conducted research in Siak Sri Indrapura Regency, the data used were primary data, secondary data and data collection techniques in the form of research with interviews and questionnaires.From the results of this study it can be concluded that, First, the Nurses Responsibility for the medical actions carried out, for negligence committed, nurses X must first obtain the delegation of authority from a Doctor who is supported in article 29 of Law Number 38 Year 2014 Regarding Nursing, and uses Law Number 36 Year 2014 Regarding Health Workers Article 68 also describes' Every individual health service action carried out by a health worker must obtain approval. Then the error of medical action carried out by the Nurse without any authority delegated oral or written from the doctor must be the responsibility borne by the Nurse as medical negligence without any delegation of authority obtained.Keywords: Nurse-Responsibility